Surface characteristics of Ni-Fe-Cr-Nb-Al-Ti coatings by supersonic particle deposition and laser remelting on AlSi12Cu alloy. (December 2020) - Han, Bingyuan; Bei, Shaoyi; Han, Guofeng; Du, Wenbo; Zhu, Sheng; Yan, Xue; Hang, Weixing; Cui, Fangfang; Du, Wei; Xu, Wenwen; Qiu, Jiaohui
Highlights: A laser remelted processing after SPD on Al-alloy is proposed. The bonding strength relies on the elastic modulus and metallurgical bonding. The phase transformation of the SPD Ni-Fe-Cr-Nb-Al-Ti coatings occurs at 800 W. The bonding strength and microhardness show a decreasing trend. The friction properties and corrosion resistance rely on the laser power. Abstract: A Ni-Fe-Cr-Nb-Al-Ti coating was prepared by the AK-02 Supersonic Particle Deposition (SPD) equipment on the substrate AlSi12Cu alloy. The prepared Ni-Fe-Cr-Nb-Al-Ti coatings were remelted under laser power of 400 W, 600 W and 800 W, respectively. The surface-interface morphologies, chemical element of the obtained Ni-Fe-Cr-Nb-Al-Ti coatings were analyzed using a scanning electron microscope (SEM) and energy dispersive spectrometer (EDS). The bonding strength was tested by dual bond tensile method. The microhardness test was carried out on HXD-1000TC hardness tester with a load of 100 g. The friction and wear resistance were carried out on CETR multifunctional friction and wear testing machine. The corrosion resistance of coatings was performed on a CS350 type electrochemical workstation. The results show that the bonding strength of the different four coatings were positively correlated with their elastic modulus and the metallurgical bonding was formed. As the distance from coatings surfaces increased, the microhardness showed a slowly decreasing trend contrarily. The friction and wear properties of the deposited and remelted coatings were also better than the deposited coating, and the friction and wear properties of the deposited and remelted coatings increased with the laser power from 400, 600 to 800 W. Compared with that of the substrate, the shifting of the coatings self corrosion potential showed that the deposited and remelted coating under laser power of 800 W had the best corrosion resistance.